Imam Ash-Shafi’i’s Opinion on Hajj without a Mahram and Its Relevance to the Present Day - Dedi, Syarial; Yuniarti, Sri (Al-Istinbath: Jurnal Hukum Islam, 2023)
This study aims to examine more deeply the opinion of Imam ash-Shafi’i regarding the pilgrimage for women without a mahram, and then see its relevance in today’s times. Imam ash-Shafi’i has opinion that a mahram or husband is not obligatory for a woman in carrying out the pilgrimage, but on condition that the woman is protected from harming her body and soul and her honor. The majority of fiqh scholars are of the opinion that women must be accompanied by their mahram to perform the pilgrimage. According to the provisions of the Shari’ah, a woman may not travel alone but must be accompanied by her husband or mahram. Even the al-Hanafiyah school of thought argues that a mahram for women is a mandatory requirement for Hajj. This study is in the form of a character study categorized as library research. It used secondary data, either in the form of primary materials, tertiary secondary. Data analysis used heuristic, critics (internal and external), interpretation, and historiography. The results of this study suggest that Imam asy-Syafi’i’s opinion which emphasizes law based on its ’illat, namely the factor of women’s safety is very relevant to current conditions.